TOWARDS LIBERALIZATION OF SERVICES IN ASEAN: CHALLENGES AND OPPORTUNITIES OF ASEAN FRAMEWORK AGREEMENT ON SERVICES (AFAS) ON TOURISM - Widiatedja, IGN Parikesit (Indonesian Journal of International Law, 2012)
The proliferation of liberalisation has been historically generated by the establishment of World Trade Organisation (WTO). Services sector was comprehensively regulated by General Agreement on Trade in Services (GATS). Regionally, AFAS was initially established to bolster the objective of GATS. In inward looking perspective, AFAS has underscored the increasing participation of ASEAN member states through strengthening their domestic services capacity, efficiency, and competitiveness. In outward looking perspective, it was intended to eliminate progressively any restrictions and internal governmental regulations in the transaction of services whose impact eventually emerged trade harassment. As a legally binding sector under GATS and AFAS, tourism is moving invariably to be one of the most dynamic sector of economic activity in ASEAN. Hence, it has cardinal role for sustainable socio-economic growth and the diversity in cultures, economy, and the complementary advantages across the region. This paper attempts to identify, decipher, and analyse meticulously challenges and opportunities of AFAS on tourism referring four modes of supplying services under article 1 of GATS encompassing: cross-border supply, consumption abroad, commercial presence, and natural persons presence. Intrinsically, ASEAN member states need to be strengthened and focused in achieving the target of a free trade area in services on tourism by 2015 as a pathway of anticipating liberalisation of services on tourism globally.